Prescription-level of tramadol utilisation at a tertiary hospital setting in Malaysia: changing trends over a 7-year follow-up period - Alias, Nor Elina; Zin, Che Suraya; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Mohd Taufek, Nor Hidayah (2019)
INTRODUCTION It was reported in a previous study that tramadol was the most frequently prescribed analgesic in Malaysia’s hospital outpatient setting. However, little is known of its trends of prescribing.